Fabrication of polysilicon nanowires using trimming technique - Uda, Hashim, Prof. Dr.; Shahrul Aizzam, Ariffin; Tijjani Adam, Shuwa (AENSI Publications, 2013)
Link to publisher's homepage at http://www.aensiweb.com/jasr.html